An Empirical Study on Mutual Funds in the U.S. Market: Performance Evaluation and Its Relation with Fund Size - Du, Lin (2008)
Mutual funds industry has grown rapidly since 1970s. As one popular type of financial intermediary, mutual fund investment becomes an important player in the financial market globally. The evaluation of mutual fund performance has been achieving a great deal of academic interest since 1960s. There has been a great deal of research which examined whether mutual funds can outperform well-diversified portfolios such as a market index. However, the findings are usually suggestive rather than conclusive. This study adopts time-series data to examine the performance of sixty three actively-managed equity growth mutual funds in the U.S. during the period from July 2003 to June 2008. The evaluation models used in this study are JensenÃÂÃÂ¢ÃÂÃÂÃÂÃÂs Alpha, SharpeÃÂÃÂ¢ÃÂÃÂÃÂÃÂs measure and TreynorÃÂÃÂ¢ÃÂÃÂÃÂÃÂs measure. These models are based on three fundamental theories: Modern Portfolio Theory, Capital Asset Pricing Model, and Efficient Market Hypothesis. The benchmark selected in this research is S&P 1500 index, which is, in particularly, used to compare with the risk-adjusted returns of sample funds. After applying one-sample T-test, the result suggests that actively-managed equity growth funds in the U.S. were able to outperform the market index during the observation period.